STATE OF SCIENTIFIC RESEARCH ON THE ISSUE OF FORMATION AND DEVELOPMENT OF LEGAL EDUCATION IN UKRAINE: PUBLIC-ADMINISTRATIVE ASPECT - Poliakova O.S. (Pressing Problems of Public Administration, 2016)
The article analyzes and systematizes works of Ukrainian scientists on problems of formation and developmentof legal education in Ukraine, the main tendencies and characteristics considering the allocationof public and administrative aspects of this problem through a setoff complementary research methods.